Ethical Packaging – a Preliminary Study - Kowalska, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The paper is a preliminary study of the concept of ethical packaging. Its main aim is to define the term “ethical packaging” and systemise a magnitude of the ethical issues surrounding packaging. A review of the literature on ethics and packaging enable the definition of such terms as business ethics, corporate ethics, Corporate Social Responsibility, Triple Bottom Line, ethical consumption, ethical eating, and sustainable packaging and provide the background for the discussion. To broaden the understanding of ethical packaging, a survey among 71 students from Maria Curie-Skłodowska University in Lublin, Poland, was conducted in 2016. The results of the survey contribute to the analysis of consumers’ perception of ethical packaging.